Studi Pengaruh Implementasi Building Information Modeling (BIM) 3D-5D Terhadap Mutu Produk Engineering dan Kinerja Waktu Pembangunan Infrastruktur Jalan Tol - Tommy Putra; Agus Suroso (Jurnal Aplikasi Teknik Sipil, 2026)
The toll road project is a construction project where each stage is quite complex and there is a potential for delays in implementation. In the era of the industrial revolution 4.0, the use of digital construction technology is highly emphasized, one of which is the implementation of BIM. BIM is becoming an important digital asset for decision-making and data. The analysis was carried out to find the influence of BIM on the quality of engineering products and the performance of implementation time using the linear regression analysis method. The results of the analysis found that there was a 73.80% influence of BIM implementation on the quality of engineering products and there was a 77.10% influence of engineering product quality on the performance of implementation time.